2020
DOI: 10.1038/s41598-020-57513-w
|View full text |Cite|
|
Sign up to set email alerts
|

Speed-dependent and mode-dependent modulations of spatiotemporal modules in human locomotion extracted via tensor decomposition

Abstract: How the central nervous system (CNS) controls many joints and muscles is a fundamental question in motor neuroscience and related research areas. An attractive hypothesis is the module hypothesis: the CNS controls groups of joints or muscles (i.e., spatial modules) by providing time-varying motor commands (i.e., temporal modules) to the spatial modules rather than controlling each joint or muscle separately. Another fundamental question is how the CNS generates numerous repertoires of movement patterns. one hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 41 publications
2
26
2
Order By: Relevance
“…Indeed, the spatial and temporal modules extracted in the two different types of techniques were related to each other (Figs. S1 and S2 ), as seen in a previous locomotion study 34 . Furthermore, the unweighted SP 4 and TE 4 modules in a gravity condition of 0.07 g were represented by the task-dependent variable close to 0 in the ST 3 module that was involved with SP 4 and TE 4 .…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Indeed, the spatial and temporal modules extracted in the two different types of techniques were related to each other (Figs. S1 and S2 ), as seen in a previous locomotion study 34 . Furthermore, the unweighted SP 4 and TE 4 modules in a gravity condition of 0.07 g were represented by the task-dependent variable close to 0 in the ST 3 module that was involved with SP 4 and TE 4 .…”
Section: Discussionsupporting
confidence: 79%
“…Thus far, we have discussed the gravity-dependent modulation of the modules at a roughly optimal walking speed corresponding to Fr ~ 0.25 in which the dynamic state of the body was geometrically similar among each gravity level because of the pendulum-like behaviour of the limbs 51 , 52 . However, not only gravitational load but also walking speed affect the generation of muscle activation patterns and their regulation based on modules 19 , 34 , 42 , 53 . As reported in previous studies, muscle activity at different walking speeds could be represented by spatial and temporal modules comparable with those at each walking speed 25 , 30 , 42 , in which task-dependent variables were systematically changed as a function of both gravity and treadmill speed in a related phase-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ), tensor decomposition enables us to analyze three factors (i.e., the column [S], row [T], and number of slices in the third dimension [K]). Previous studies have shown the effectiveness of tensor decomposition and its variants in discussing task-dependent effects on spatiotemporal muscle modules 23 25 . We thus expect to discuss how spatiotemporal modules show effort-dependent effects by using tensor decomposition for each subject.…”
Section: Introductionmentioning
confidence: 99%